Protocol for quantifying muscle fiber size, number, and central nucleation of mouse skeletal muscle cross-sections using Myotally software - Pieter Both; Soochi Kim; Jengmin Kang; Marina Arjona; Daniel I. Benjamin; Christopher W. Nutter; Armon Goshayeshi; Thomas A. Rando (STAR Protocols)
Summary: Here, we present a protocol for using Myotally, a user-friendly software for fast, automated quantification of muscle fiber size, number, and central nucleation from immunofluorescent stains of mouse skeletal muscle cross-sections. We describe steps for installing the software, preparing compatible images, finding the file path, and selecting key parameters like image quality and size limits. We also detail optional features, such as measuring mean fluorescence. By automating these traditionally labor-intensive processes, Myotally improves research efficiency and data consistency. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.